Theoretical and empirical limits of Scandinavian Exceptionalism: isolation and normalization in Danish prisons - Reiter, Keramet (Punishment & society, 2018)
Drawing on interviews with 76 prisoners, 47 prison staff, and 14 experts, we document lived experiences of punishment in the Danish prison context. We argue that, regardless of “humanizing” elements of normalization and humanity, prisoners and staff may experience the power of the carceral state in Denmark in ways similar to those under more obviously harsh confinement regimes, as exist in the United States and, to a lesser extent, in the United Kingdom. Ultimately, macro-level theories like Scandinavian Exceptionalism serve as a rhetorical tool, implying that harsher prison systems are fixable, but fail to reflect the micro-level realities of incarceration.